2008
DOI: 10.2147/nsa.s3571
|View full text |Cite
|
Sign up to set email alerts
|

<em>Vibrio fischeri</em> and <em>Escherichia coli</em> adhesion tendencies towards photolithographically modified nanosmooth poly (<em>tert</em>-butyl methacrylate) polymer surfaces

Abstract: This study reports the adhesion behavior of two bacterial species, Vibrio fi scheri and Escherichia coli, to the photoresistant poly(tert-butyl methacrylate) (P(tBMA)) polymer surface. The data has demonstrated that ultraviolet irradiation of P(tBMA) was able to provide control over bacterial adhesion tendencies. Following photolithography, several of the surface characteristics of P(tBMA) were found to be altered. Atomic force microscopy analysis indicated that photolithographically modifi ed P(tBMA) (hencefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
3
2
0
Order By: Relevance
“…It is believed that EPS production is essential in facilitating the initial stages of bacterial attachment to various surfaces (8,13). Our recent studies on bacterial attachment to nanosmooth glass surfaces and to poly(tert-butyl methacrylate) (P(tBMA)) polymeric surfaces were in agreement with this concept: Enhanced bacterial attachment was accompanied by elevated levels of secreted extracellular polymeric materials (9,10,13). In this study the shift in production of low amounts of EPS might be also due to the low carbon/nitrogen ratio as it was previously reported that EPS production is strongly dependent on the carbon/nitrogen ratio of the nutrient medium (5).…”
Section: Discussionsupporting
confidence: 59%
“…It is believed that EPS production is essential in facilitating the initial stages of bacterial attachment to various surfaces (8,13). Our recent studies on bacterial attachment to nanosmooth glass surfaces and to poly(tert-butyl methacrylate) (P(tBMA)) polymeric surfaces were in agreement with this concept: Enhanced bacterial attachment was accompanied by elevated levels of secreted extracellular polymeric materials (9,10,13). In this study the shift in production of low amounts of EPS might be also due to the low carbon/nitrogen ratio as it was previously reported that EPS production is strongly dependent on the carbon/nitrogen ratio of the nutrient medium (5).…”
Section: Discussionsupporting
confidence: 59%
“…The largely pH-independent ζ-potential values measured in this work (Table 1) are in good agreement with the −30.1 ± 9 mV previously reported for V. fischeri (DSM 507 strain) at pH 7.2 [59]. In particular, the near-constant surface charge observed for V. fischeri cells grown in the media at pH 6, 7, or 8, i.e., under conditions analogous to those of the long-term cell-growth and bioluminescence measurements in Figure 1, implies that the suppressed growth at pH 6 did not result from dramatic changes in the electrostatic environment of cell surfaces.…”
Section: Surface Charge Of V Fischeri Is Ph-independentsupporting
confidence: 91%
“…The observed variations in the mean diameter values were not statistically significant among the timepoints, with an overall mean diameter of 0.6 ± 0.1 µm. The mean length observed in this work was at the lower and upper limits, respectively, of the previous literature values for V. fischeri cells measured using optical microscopy (2-3 µm) [27,32] and SEM (1.5-2 µm) [59]. The overall larger values obtained using optical microscopy were likely due to the shrinking of bacterial cells that commonly results from their preparation for SEM imaging, which includes fixation with glutaraldehyde and dehydration in ethanol and in the critical-point dryer [61].…”
Section: Typical Morphology Of V Fischeri Cellssupporting
confidence: 68%
“…As the interaction with the cellular membrane seems to be the main factor that explains the biological activity of CFA and its Eu(III) complexes, a detailed study was performed in order to obtain further insight into the compound–membrane interactions. This study was performed by electrophoretic mobility, a commonly used technique for surface characterization of nonbiological colloids and, more recently, bacterial, yeast or animal cells [ 73 ]. The determination of the surface charge of living cells ( δ ) is of prominent importance for understanding their behaviour and functions under various environmental conditions.…”
Section: Resultsmentioning
confidence: 99%